Cytoplasmic Travels of the Ecdysteroid Receptor in Target Cells: Pathways for both Genomic and Non-Genomic Actions - Vafopoulou, Xanthe; Steel, Colin G. (Frontiers in Endocrinology, 2012)
ABSTRACT Signal transduction of the insect steroid hormones, ecdysteroids, is mediated by the ecdysteroid receptor, EcR. In various cells of the insect Rhodnius prolixus, EcR is present in both the nucleus and the cytoplasm, where it undergoes daily cycling in abundance and cellular location at particular developmental times of the last larval instar that are specific to different cell types. EcR favors a cytoplasmic location in the day and a nuclear location in the night. In double and triple labels using several antibodies, immunohistochemistry and confocal laser scanning microscopy, we identified intimate associations of EcR with the microtubules (MTs). Treatments with either the MT stabilizing agent taxol or with colchicine which depolymerises MTs, resulted in considerable reduction in nuclear EcR with a concomitant increase in cytoplasmic EcR suggesting that MT disruption inhibits receptor accumulation in the nucleus. EcR also forms intimate associations with the chaperone Hsp90, the immunophilin FKBP52 and the light chain 1 of the motor protein dynein. All these factors also associate with MTs. We propose that in Rhodnius, EcR exerts its genomic effects by forming a complex with Hsp90 and FKBP52 which uses dynein on MTs as a mechanism for daily nucleocytoplasmic shuttling. The complex is transported intact to the nucleus and dissociates within it. We conclude that EcR utilizes the cytoskeletal tracks for movement in a manner closely similar to that used by the glucocorticoid receptor. This is the first study to examine the mechanism of intracellular transport of EcR and reveals close similarities with some of its mammalian counterparts. We also observed close associations of EcR with mitochondria which raise the possibility that EcR, like its mammalian counterparts, may be involved in the coordination of non-genomic responses of ecdysteroids in mitochondria.